Amelioration of methotrexate-induced enteritis by melatonin in rats - ŞENER, GÖKSEL (WILEY, 2004)
The anti-tumour drug methotrexate (MTX) induces intestinal mucosa injury resulting in malabsorption and diarrhoea. The purpose of this study wag to investigate whether exogenous melatonin could protect the gut from MTX-induced damage in rats. A single dose of MTX (20 mg kg(-1), i.p.) was followed by i.p. saline or melatonin injections (10 mg kg(-1), MTX + Mel) for the next 5 days. On the fifth day, intestinal transit was assessed using charcoal propagation. Rats were decapitated and small intestinal segments were fixed for light (LM) and scanning electron microscope (SEM) examinations. Other intestinal segments were stored to measure glutathione (GSH) and malondialdehyde (MDA) levels, myeloperoxidase (MPO) and ATPase activity. MTX led to loss of more than 10% of the initial body weight (p < 0.01). Conversely, weight loss was markedly less in the melatonin-treated MTX group (p < 0.05). Bowel motility was increased in MTX-treated rats, while the transit index in the MTX-Mel group was not different from the control group. MTX caused decreases in GSH levels and ATPase activity. with increases in MDA levels and MPO activity. These changes were reversed in MTX-Mel-treated rats (p < 0.05-p < 0.001). LM and SEM in the MTX group revealed desquamation of surface epithelium and glandular degeneration, while the epithelium was slightly damaged in the MTX-Mel group. In conclusion, the present study demonstrates that melatonin is capable of reversing MTX-induced intestinal dysfunctions, indicating that it may be beneficial in ameliorating the symptoms of chemotherapy-induced enteritis. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: methotrexate; melatonin; enteritis; myeloperoxidase activity; Na+-K+-ATPase activity; SMALL-INTESTINE; OXIDATIVE STRESS; DAMAGE; ACID; CELL; DEHYDROGENASES; LOCALIZATION; TRANSPORT